The Routledge handbook of pragmatics - Barron, Anne; Gu, Yueguo; Steen, Gerard (Routledge handbooks in applied linguistics, 2017)
The Routledge Handbook of Pragmatics provides a state-of-the-art overview of the wide breadth of research in pragmatics. An introductory section outlines a brief history, the main issues and key approaches and perspectives in the field, followed by a thought-provoking introductory chapter on interdisciplinarity by Jacob L. Mey. A further thirty-eight chapters cover both traditional and newer areas of pragmatic research, divided into four sections: Methods and modalities, Established fields, Pragmatics across disciplines, Applications of pragmatic research in today’s world. With accessible, refreshing descriptions and discussions, and with a look towards future directions, this Handbook is an essential resource for advanced undergraduates, postgraduates and researchers in pragmatics within English language and linguistics and communication studies.